2007
DOI: 10.1016/j.addbeh.2007.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of alcohol use during the first year of college: Implications for prevention

Abstract: The first year of college is a unique transition period, in which the student establishes a college identity and social network. Alcohol use is often part of this process, and many first-year college students develop a pattern of heavy drinking that puts them at risk for adverse consequences during their college years and into young adulthood. To better understand the development of risky alcohol use during this transition, we reviewed the literature on influences on college drinking and identified moderators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
302
1
10

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 358 publications
(331 citation statements)
references
References 150 publications
(169 reference statements)
18
302
1
10
Order By: Relevance
“…A recent review of the literature has been conducted in the United States for alcohol use (Borsari et al, 2007) and another was conducted for HED in Europe specifically, but for the general population (Kuntsche et al, 2004). These reviews list many identified risk factors for alcohol use and HED, including one particular class of risk factors, perceived norms, that has the potential to be useful for prevention purposes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review of the literature has been conducted in the United States for alcohol use (Borsari et al, 2007) and another was conducted for HED in Europe specifically, but for the general population (Kuntsche et al, 2004). These reviews list many identified risk factors for alcohol use and HED, including one particular class of risk factors, perceived norms, that has the potential to be useful for prevention purposes.…”
mentioning
confidence: 99%
“…Factors other than perceived norms identified for alcohol use among higher education students include gender, alcohol expectancies and drinking motives, perceived harm, other substance use and academic discipline (Borsari et al, 2007;Cameron and Campo, 2006;Kuntsche et al, 2004;Sher and Rutledge, 2007;Webb et al, 1997).…”
mentioning
confidence: 99%
“…26 An injury in the brain parts may lead to the functional abnormalities which can further associated with the lower academic performance and affect the learning and cognitive functions. 27,28 Toumbourou et al 29 reported that unsafe use of alcohol caused approximate 31.5% of deaths among 15-29 year persons worldwide. In the present study, we have found that the maximum drinkers started drinking at the age of 16 years or above but the percentage of drinkers under the age of 15 are also remarkable and indicates an alarming situation.…”
Section: Discussionmentioning
confidence: 99%
“…College student drinking has received a great deal of research attention, with the bulk of this work examining White students (Borsari et al, 2007). To date, few studies have focused on ethnic minority groups such as Mexican Americans, who comprise two thirds of the U.S. Hispanic population (U.S. Census Bureau, 2010).…”
mentioning
confidence: 99%
“…Temperament (i.e., behavior undercontrol and negative emotionality), male gender, White race, and positive anticipated effects of alcohol use (expectancies) have all been found to reliably predict increases in drinking (Borsari et al, 2007). Differences in drinking rates among ethnic groups may refl ect cultural practices and identity.…”
mentioning
confidence: 99%